Performance gains in relay swimming (part 1): the relay start benefit component - Qiu, X.; Braun, C.; Fischer, S.; Kibele, A. (ISBS Proceedings Archive (Michigan), 2022)
The present study aimed to detect statistical differences in the start performance between relay and individual races accounting for gender and relay start techniques. Race data of relay races and corresponding individual races from European Championships (2019) were analysed. Linear mixed models for repeated measures were applied to compare the differences in the 15 m start times (after toe-off) between relay and individual races accounting for gender and relay start techniques. The results revealed a small time benefit for step-starts over no-step starts in the freestyle races. Furthermore, depending on techniques, male butterfly swimmers showed more pronounced differences in their start performance as compared to female swimmers. However, no statistical differences were found in breaststroke races for either gender or relay start technique. The findings of the present study may improve coaches' and swimmers' understanding of the downsides and benefits of different relay starts. Based on results, we suggest that, at least for freestyle relays, a step-start should be the relay start technique of choice.